The role of influencers in purchase intention along the context of product involvement - Costa, Bárbara Teixeira Fernandes Garcez da (2022)
Influencers have captured the attention of many brands who are looking to drive sales through digital communication sources, thus achieving higher returns on their investments. Although it is not a new concept, influencer marketing is still a fast growing market. Despite the fact that many marketeers are spending high portions of their budget on influencer marketing, there is currently lack of insight on the substantial impacts of Influencers on consumer attitudes. Notwithstanding, many researchers have explored this concept under distinct scopes. Still, there is a need to further investigate this research topic in novel contexts, particularly under the light of different product categories. Hence, this research study intends to understand the impact of Influencers’ perceived expertise and their effectiveness as an information source in consumers’ purchase intention, by integrating the moderating role of product involvement. In order to reach conclusions regarding consumer’s decision-making process and attitudes towards Influencers, the study analyses the responses of 267 survey participants through descriptive analysis and multiple linear regression models. The results show evidence that Influencer’s perceived expertise is an important determinant of purchase intention on both the high and low involvement products elected for this research. Additionally, it is concluded that Influencer sponsorships show influence on purchase intention of both products. High involvement moderates the relationship between Influencer’s perceived expertise and purchase intention, whereas low involvement is not a moderator of this relationship. Thus, when it comes to planning influencer marketing campaigns, this dissertation advises companies to take into consideration the product being marketed, its price point, and the choice of an Influencer aligned with the company’s industry and with expertise in the endorsed product.